Human rights and political crisis in Brazil: Public health impacts and challenges. Issue 11 (2nd November 2018) - Malta, Monica
ABSTRACT: In 31 August 2016, Brazilian president Dilma Rousseff was impeached and replaced by her vice president Michel Temer. Herein, we examine how the conservative agenda of Mr Temer and his supporters is influencing key decisions in the human rights and public health arena in Brazil. The government's austerity agenda includes severe cuts in critical areas such as health, education and science, jeopardising well-known strategies such as the Brazilian Public Health System (SUS) and nationwide cash transfer program, 'Bolsa Familia' – both benefited millions and were the largest of their kind in the world. Mr Temer's decisions show not only severe cuts in critical areas but also a political agenda that clearly demonstrates a broad shift away from the progressivism and social agenda presented and supported by its predecessors. Most vulnerable groups such as the LGBTQ community, women, people who use drugs and disenfranchised communities have been severely affected. Mr Temer's administration is putting Brazil far from its once nationwide goal to foster free and universal health care access and social equity for all its citizens. The near future for Brazil is unknown, but both national and international communities anticipate severe problems within the national human rights arena, if nothing changes. Abbreviations: CCT: Conditional Cash Transfer; LGBTQ: Lesbian, Gay, Bisexual, Transgender and Queer (and/or Questioning); SUS: Brazilian Public Health System